Development of Dual ARV-825 and Nintedanib-Loaded PEGylated Nano-Liposomes for Synergistic Efficacy in Vemurafnib-Resistant Melanoma - Yige Fu; Aishwarya Saraswat; Zenghui Wei; Manas Yogendra Agrawal; Vikas V. Dukhande; Sandra E. Reznik; Ketan Patel (MDPI AG, 2021)
A novel treatment strategy by co-targeting c-Myc and tumor stroma was explored in vemurafenib-resistant melanoma. BRD4 proteolysis targeting chimera (ARV-825) and nintedanib co-loaded PEGylated nanoliposomes (ARNIPL) were developed to incorporate a synergistic cytotoxic ratio. Both the molecules have extremely poor aqueous solubility. A modified hydration method with citric acid was used to improve the loading of both the molecules in liposomes. ARNIPL with mean particle size 111.1 ± 6.55 nm exhibited more than 90% encapsulation efficiency for both the drugs and was found to be physically stable for a month at 4 °C. Both the molecules and ARNIPL showed significantly higher cytotoxicity, apoptosis and down-regulation of target proteins BRD4 and c-Myc in vemurafenib-resistant cell line (A375R). Vasculogenic mimicry and clonogenic potential of A375R were significantly inhibited by ARNIPL. Tumor growth inhibition in 3D spheroids with reduction of TGF-β1 was observed with ARNIPL treatment. Therefore, ARNIPL could be a promising therapeutic approach for the treatment of vemurafenib-resistant melanoma.